Postindustrialism and postmaterialism? A critical view of the new economy, the information age, the high tech society and all that - Harold L. Wilensky (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
The theory of postindustrial society and postmaterialist culture can explain neither the structural uniformities of modern society captured by convergence theory nor the national differences captured by theories of democratic corporatism and the mass society. Its depiction of structural changes is superficial: the service sector is too heterogeneous to describe occupational and industrial trends; the idea of technocratic dominance is overblown and misses big national differences in the location and role of experts and intellectuals. As for postindustrial values, they apply to a small population, a minority even of college students. That these attitudes fluctuate so much with shifting economic conditions and political agendas casts doubt on the idea of a basic shift toward 'postmaterial values'. The literature documenting such shifts is plagued with problems of survey validity. It goes up against a heavy weight of evidence showing that older issues of security, equality, civic order and crime, economic growth and stability are dominant in the politics and mentality of modern populations; that cohort effects are weak to non-existent; that political generational effects are rare and soon fade away; that family life cycle, if carefully delineated, has an impact across a wide range of attitudes and behavior. Most important, differences in national mobilizing structures shape both mass and elite responses to the dilemmas and problems of modern life. Assessing related images of modern society - 'the information age', the 'high-tech society' - the paper finds these equally misleading. This paper is based on chs. 1 and 4 of H.L. Wilensky, Rich Democracies: Political Economy, Public Policy, and Performance (University of California Press, 2002).
Keywords: 300